1997
DOI: 10.1046/j.1365-2141.1997.492695.x
|View full text |Cite
|
Sign up to set email alerts
|

Colony counting is a major source of variation in CFU‐GM results between centres

Abstract: Summary.The results for colony forming unit granulocytemacrophage (CFU-GM) assays vary substantially between centres. It is possible that colony counting is largely responsible for this discrepancy. In order to examine this exclusively from the many factors that make up the CFU-GM assay, we performed a colony counting exercise involving 11 laboratories. Two-way analysis of variance showed a highly significant difference (P ¼ 0 : 0001) in the counts obtained from the centres. One centre was found to score consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Despite the numerous alternatives for viability estimation available as stated in the introductory part, most studies focussing on the cryopreservation of C. vulgaris use conventional plating and cell counting techniques. The relative standard errors of these were, if given at all, in the range of 1.6‐88% , giving, as formerly reported , rise to the conclusion that direct comparability between different studies is difficult. In comparison, the newly introduced growth pattern analysis approach reproducibly achieved < 5% of relative standard error, thereby providing robust and rapid access to well resolved and valid viability data.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Despite the numerous alternatives for viability estimation available as stated in the introductory part, most studies focussing on the cryopreservation of C. vulgaris use conventional plating and cell counting techniques. The relative standard errors of these were, if given at all, in the range of 1.6‐88% , giving, as formerly reported , rise to the conclusion that direct comparability between different studies is difficult. In comparison, the newly introduced growth pattern analysis approach reproducibly achieved < 5% of relative standard error, thereby providing robust and rapid access to well resolved and valid viability data.…”
Section: Resultsmentioning
confidence: 64%
“…Since the counting of colony forming units as the best established method for viability determination is known to be error‐prone , this study aimed to introduce a novel approach which is based on the comparative evaluation of online mo‐nitored growth patterns which are obtained from microtiter plate cultivations. The underlying idea is that cultures with reduced viability need more time to reproduce compared to a reference cultivation with 100% viability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…User bias in methods that involve manual counting is a known source of data variation 24 , especially between institutions 25 . The use of this automated method eliminates this possibility while simultaneously improving consistency.…”
Section: Discussionmentioning
confidence: 99%
“…The main issue regarding clonogenic survival assays is represented by inter-and intra-operator variability, nevertheless, clonogenic assay is still considered as a well-established technique to identify clonogenic cells after a specific cell treatment [3]. This concern affects each technique based on manual counting and thus also the colony formation assay [4]. However, an extensive analysis of several clonogenic assay results has been recently carried out and it demonstrated that, despite inter-operator differences, clonogenic assays can be still considered as a robust method to study the ability of cells to form colonies [5].…”
Section: Introductionmentioning
confidence: 99%